2021
DOI: 10.1111/1911-3838.12265
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Not to Be: Blockchain and the Future of Accounting and Auditing*

Abstract: The purpose of this article is to study the potential impact of blockchain technology on accounting systems and businesses. Blockchain technology characteristics and operating modes have the potential to bring about innovations to the fields of accounting and auditing. After describing the function of blockchain technology, we examine potential accounting transformations and identify how the deployment of this technology might impact accountants and external auditors. To that end, we review the literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…In the classroom, when the teacher asks a question or gives instructions to designate a student to speak, students usually choose to respond, so the passive response is a student language behaviour that occurs more often, and for students with a good degree, the verbal behaviour of taking the initiative to answer questions also occurs. In the interviews, students indicated that they would ask the teacher questions when they encountered problems, but not in the classroom, usually during class or in the teacher's office by themselves, so this behaviour was not observed in the classroom [20]. e number of times the student-student interaction behaviour of student-peer discussion occurred in the video was zero.…”
Section: Analysis Of the Construction Of Cooperative Curriculum Syste...mentioning
confidence: 99%
“…In the classroom, when the teacher asks a question or gives instructions to designate a student to speak, students usually choose to respond, so the passive response is a student language behaviour that occurs more often, and for students with a good degree, the verbal behaviour of taking the initiative to answer questions also occurs. In the interviews, students indicated that they would ask the teacher questions when they encountered problems, but not in the classroom, usually during class or in the teacher's office by themselves, so this behaviour was not observed in the classroom [20]. e number of times the student-student interaction behaviour of student-peer discussion occurred in the video was zero.…”
Section: Analysis Of the Construction Of Cooperative Curriculum Syste...mentioning
confidence: 99%
“…Chaque bloc portant le numéro de hash du précédent bloc, il est impossible d'intervertir des blocs. Le schéma suivant proposé par Desplebin et al (2021) résume le fonctionnement de ce réseau (cf. figure 1).…”
Section: Caractéristiques Et Principes De Fonctionnementunclassified
“…While some scholars recognise that blockchain relates more to cryptography than accounting (Gietzmann and Grossetti, 2021), blockchain is crucial because it can transform accounting techniques and processes (Desplebin et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While some scholars recognise that blockchain relates more to cryptography than accounting (Gietzmann and Grossetti, 2021), blockchain is crucial because it can transform accounting techniques and processes (Desplebin et al, 2021). Several forums, conferences and special issues address the changing landscape of accounting, auditing and accountability in the face of disruptive technologies.…”
Section: Introductionmentioning
confidence: 99%